Investigation on micro-residual stress distribution near hole using nanoindentation: Effect of drilling speed. (November 2019) - Tiwari, Abhishek Kumar; Kumar, Amit; Kumar, Navin; Prakash, Chander
Residual stresses are induced in the material during manufacturing operations, which considerably affect the fatigue performance and the lifespan of a mechanical work piece. The nature, magnitude, and distribution of residual stresses decide their beneficial or detrimental effects. Past research efforts concluded that mechanical process parameters influence residual stress nature, distribution, and the magnitude. Nevertheless, how residual stress generation depends on the process parameters, is not well investigated especially in the case of a drilling operation. In fact, the residual stress field is required to be regulated near drilled holes to improve the fatigue strength of structural joints, especially in the aircraft industry. Accordingly, this work attempts to estimate the drilling-induced micro-residual stress distribution near the drilled hole. In addition, the effect of drilling speed on residual stress distribution has also been studied. A nanoindentation technique is used to follow-up precise distribution of micro-residual stresses near the holes drilled at three different drilling speeds of 700, 900, and 1100 r/min. The outcomes indicate the presence of compressive residual stresses near the hole. In addition, an increase in residual stress level is noticed with an increase in the drilling speed up to 900 r/min. A uniform distribution of residual stresses is observed near the hole when drilled at a higher drilling speed of 1100 r/min. These findings may be useful in planning an improved drilling operation to produce beneficial residual stress distribution. This may ultimately improve the fatigue strength and the service life of mechanical components or structures with drilled holes.